2015
DOI: 10.1542/peds.2014-2941
|View full text |Cite
|
Sign up to set email alerts
|

13-Valent Pneumococcal Conjugate Vaccine (PCV13) in Preterm Versus Term Infants

Abstract: OBJECTIVES: This study evaluated the immune response and safety profile of 13-valent pneumococcal conjugate vaccine (PCV13) in preterm infants compared with term infants.METHODS: This Phase IV, open-label, 2-arm, multicenter, parallel-group study enrolled 200 healthy infants (preterm, n = 100; term, n = 100) aged 42 to 98 days. All subjects received PCV13 at ages 2, 3, 4 (infant series), and 12 (toddler dose [TD]) months, together with routine vaccines (diphtheriatetanus-acellular pertussis, hepatitis B, inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 25 publications
5
11
0
4
Order By: Relevance
“…[4][5][6] The immunogenicity of PCV13 in premature infants receiving a 2-3-4 and 12-month schedule was only recently reported and revealed lower immunoglobulin G (IgG) concentrations for 8 serotypes after both primary and booster doses compared with term infants. 7 This lower immunogenicity is consistent with previous PCV7 studies 8 -10 and is concerning because premature infants are also less likely to benefit from the protective maternal antibodies transferred during late pregnancy.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…[4][5][6] The immunogenicity of PCV13 in premature infants receiving a 2-3-4 and 12-month schedule was only recently reported and revealed lower immunoglobulin G (IgG) concentrations for 8 serotypes after both primary and booster doses compared with term infants. 7 This lower immunogenicity is consistent with previous PCV7 studies 8 -10 and is concerning because premature infants are also less likely to benefit from the protective maternal antibodies transferred during late pregnancy.…”
supporting
confidence: 87%
“…4,21 However, compared with previous term (PCV13) and preterm (PCV7) studies, antibody concentrations after primary and booster vaccination are lower overall, resulting in lower seroprotection after primary vaccination. 4,5,8,9,22 Similarly, compared with the recent PCV13 preterm study, 7 lower IgG GMCs and seroprotection rates were seen for all serotypes. These differences may be due to the different laboratory testing methods used for serotype-specific antibody concentrations, but potential biological explanations include interactions with concurrently administered vaccines, the younger gestation of the study cohort, or our broad inclusion criteria encompassing infants with complex medical problems (representative of the preterm population).…”
Section: Discussionmentioning
confidence: 74%
“…However, the majority of preterm infants achieved both pneumococcal serotype-specific IgG antibody levels threshold of protection. 46 In summary, lower vaccine pneumococcal serotypes IgG GMTs were found in preterm infants for primary doses. Accordingly French and Canadian recommendations advocate a regimen of 4 doses (consisting of 3 primary doses with a toddler booster dose) of pneumococcal conjugate vaccines for the routine immunization of preterm infants rather than the 2 C 1 regimen.…”
Section: Acellular Pertussismentioning
confidence: 89%
“…Despite this increased risk for infection, vaccination of preterm infants is often delayed [65]. A clinical trial was conducted to evaluate the immune response and safety profile of the 13-valent pneumococcal conjugate vaccine (PCV13) in preterm compared to term infants on the same vaccination schedule [66]. Two hundred healthy infants (preterm, n=100, term, n=100) between 42 and 98 days postnatal age were enrolled in a phase 4, open label, multicenter parallel-group study.…”
Section: Hivmentioning
confidence: 99%
“…The vaccination was tolerated well regardless of gestational age. The investigators concluded that majority of subjects in both groups were able to exceed the World Health Organization threshold of protection and functional antibody response after the infant series [66]. …”
Section: Hivmentioning
confidence: 99%